A case for camp-scale seismic for IOCG exploration - Kepic, Anton; Okan, E. (2016)
We propose that the best means to discover new Iron-Oxide-Copper-Gold deposits that do not have strong gravity or magnetic signatures under cover, such as those found in the Gawler Craton in South Australia, is to use the 3D seismic reflection method with sparse survey parameters. We use the Olympic Dam deposit as a n example of such a strategy. Previous 2D seismic surveys can detect the Olympic Dam breccia complex. So could 3D seismic surveys be cost effective versus drilling blindly to find others nearby? Our findings with the Olympic Dam case study demonstrate that the 3D seismic reflection method is viable in detecting these large mineralised systems, and cost effective versus sparse grid drilling.